Instructional Design For Teaching Writing At Department English Education At Muhammadiyah University Of Surakarta - , Handoko; , Prof. Dr. Endang Fauziati, M. Hum; , Dr. Dwi Haryanti, M.Hum (2014)
The study is aimed at observing the instructional desgin for teaching writing at Muhammadiyah University of Surakarta. In this research, there are nine component of instructional design, namely: (1) learning objective. (2) syllabus. (3)roles of instructional material. (4) classroom procedure. (5) classroom technique (6) teacher's role. (7) learner's role. (8) media. (9) assessmentmodel. The type of the study is descriptive qualitative. In this research, the data are devired from event, informant, and field note. There are three techniques of collecting data, namely: observation, interview, and document. The techniques of analyzing data are data reduction, data display, and verification/conclusion. The result of the study, such as: (1) There are two learning objective of teaching writing espesially in teaching writing namely: general objective and specific objective. In general learning objective based on competence standard is taken from syllabus. In specific learning objective of teaching English is written in basic competence is taken from syllabus (2) The type of syllabus is structural or grammatical syllabus.(3)The instructional material of writing is based on the syllabus, the lecturers uses printed material which taken from writing 1 student's copiesbook. The material of writing skill in Muhammadiyah University of Surakarta is paragraph text such procedure text. (4) the classroom procedure used is 5E (Engagement, Exploration, Explanation, Elaboration and Evaluation) and (Exploration, Explanation, Evaluation) (5) teaching technique used in teaching English are The lecturer uses some techniques in prewriting such as brainstorming, free writing, questioning, listing, and clustering. It discusses a topic about procedure text, probes in prewriting, drafting, and revising. The lecturer uses the instructor feedback and peer-editing. (6) The teacher's role are as facilitator,as classroom manager, as instructor, as consultant, and as evaluator.(7) the learner's role arelearners monitor and evaluate their own progress, learners learn from the lecturer and learners from the student's presentation. (8) The media used in teaching learning process is used student's copybook as printed media (9) assessment model used are homework, mid test and final test.